1990
DOI: 10.1021/bi00476a023
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between perdeuterated dimyristoylphosphatidylcholine and low molecular weight pulmonary surfactant protein SP-C

Abstract: A low molecular weight hydrophobic protein was isolated from porcine lung lavage fluid using silicic acid and Sephadex LH-20 chromatography. The protein migrated with an apparent molecular weight of 5000-6000 on SDS-PAGE under reducing and nonreducing conditions. Gels run under reducing conditions also showed a minor band migrating with a molecular weight of 12,000. Amino acid compositional analysis and sequencing data suggest that this protein preparation contains intact surfactant protein SP-C and about 30% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
61
3

Year Published

1991
1991
2001
2001

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(77 citation statements)
references
References 43 publications
13
61
3
Order By: Relevance
“…This affords a molecular explanation of the recent finding that SP-C is predominantly monomeric in fluid DPPC/ dipalmitoylphosphatidylglycerol (DPPG) vesicles, but undergoes self-aggregation in the same lipid mixture below the transition temperature between gel phase and liquid-crystalline phase [38]. Accordingly, the decrease of the phase transition temperature of phospholipid vesicles caused by SP-C [10] may be due to peptide aggregates disrupting the lipid packing in the gel phase.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…This affords a molecular explanation of the recent finding that SP-C is predominantly monomeric in fluid DPPC/ dipalmitoylphosphatidylglycerol (DPPG) vesicles, but undergoes self-aggregation in the same lipid mixture below the transition temperature between gel phase and liquid-crystalline phase [38]. Accordingly, the decrease of the phase transition temperature of phospholipid vesicles caused by SP-C [10] may be due to peptide aggregates disrupting the lipid packing in the gel phase.…”
Section: Discussionmentioning
confidence: 79%
“…These 'lamellar bodies' are excreted into the alveolar liquid subphase, where they are converted into more complex bilayer structures ('tubular myelin'), from which the surfaceactive monolayers are eventually formed. SP-C is thought to have an important role in facilitating the conversion of subphase bilayer structures into surface-active DPPC monolayers at the air/liquid interface [5][6][7][8][9][10]. Since large-scale production of natural SP-B and SP-C is difficult, the development of synthetic, possibly non-peptide analogs for therapeutic purposes is of great potential interest [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…These effects were increased by the simultaneous presence of Ca 2+ and PG. Other biophysical measurements [279], although not conclusive, suggested that SP-C might increase lipid adsorption, by inducing the formation of non-bilayer lipid structures. Using fluorescent phospholipid probes, HOROWITZ et al [280] found that SP-C orders the bilayer surface, but disrupts the interior acyl chain packing.…”
Section: Functional Correlationsmentioning
confidence: 92%
“…In contrast to the nearperfect fit between SP-C and a fluid Pam,GroPCho bilayer, the peptide appears poorly suited to be incorporated into a gel-phase Pam,GroPCho bilayer, with an approximate thickness of 3.9 nm of the hydrocarbon part alone (Zhang et al, 1992), or a phospholipid monolayer, unless it is significantly tilted from a normal to the bilayerlmonolayer plane. Simatos et al (1990) showed by WNMR spectroscopy that SP-C has no effect on lipid chain order in the liquid-crystal phase but reduced orientational order in the gel phase. In gel-phase lipids, the SP-C helix is significantly shorter than the thickness of the lipids and such mismatches promote phase separations of peptides and lipids (Zhang et al, 1992).…”
Section: Protein-lipid Interactions In Surfactantmentioning
confidence: 99%